Uso de crambe no controle de sitophilus zeamais mots. Em milho armazenado - Simonetti, Ana Paula Morais Mourão (2017)
Maize has been of great importance as a cereal for the whole Brazilian, but not all harvested grains are used immediately, so much of the production is stored. So, pests are among the factors that affect the quality of stored grains. Sitophilus zeamais has been one of the biggest causes of losses, both in quantitative and qualitative for grains and seeds. Thus, pesticides usually applied to control this weevil can poison the applicators and cause pest resistance or even environmental damage. Therefore, there is an investigation for less aggressive alternatives as a control, and one of them is applying plants with insecticidal or repellent potential. So, this trial aimed at evaluating the effect powder, aqueous extracts and hydroalcoholic extracts of Crambe abyssinica on their survival, emergence, mortality and attractiveness of Sitophilus zeamais, besides its effects on corn seeds treated with this extract. This research was divided into three stages: the first one tested powder and aqueous extracts of crambe at 0%, 1%, 2%, 3% and 4% concentrations in survival, emergence, mortality, attractiveness, repellency and insecticidal action. During the second stage, the same concentrations of crambe extract were tested as in the other ones, but with a hydroalcoholic extract; in order to evaluate survival, emergence, mortality and insecticidal effect on Sitophilus Zeamais. The best effective results were observed with the application of crambe hydroalcohol extracts. The third step evaluated the use of these hydroalcoholic extracts in the following concentrations: 0%, 5%, 15% and 25% concerning attractiveness and insecticidal effect on insects, besides the physiological quality of corn seeds. The obtained results allowed the following conclusions: 1. aqueous extract of crambe grains provides less survival and emergence percentages of Sitophilus zeamais as well as lower consumption of treated corn grains, in relation to the use of crambe grain powder. 2. The hydroalcoholic extract of crambe has insecticidal potential on Sitophilus zeamais, and as concentration increases, from 0 to 4%, the results are more effective. It is also less attractive to the insect, since it provided a decrease in the number of corn grains infested by the pest and the number of insects that emerged from these grains in relation to its non-use. 3. 25% concentration of hydroalcoholic extract in crambe grains yields a high mortality rate (65%); 4. 15% concentration of hydroalcoholic extract in crambe grains stimulates germination percentage, normal seedlings and mass of corn seedlings; 5. 25% concentration hydroalcoholic extract of crambe grains does not negatively influence germination or initial development parameters of maize; and 6. Maize treated with hydroalcohol extract of crambe, stored until 60 days, stimulates germination, mass and length of maize seedlings. Therefore, new research is suggested to develop commercial product based on hydroalcoholic extract of crambe at 25% concentration.